2009
DOI: 10.1002/adsc.200800807
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid‐Catalyzed Synthesis of Functionalized Pyrroles

Abstract: The synthesis of highly functionalized pyrroles is described. The sequence involves the preliminary preparation of a-aminohydrazones by Michael addition of primary amines to 1,2-diaza-1,3-butadienes. The treatment of these compounds with dialkyl acetylenedicarboxylates produces a-(Nenamino)-hydrazones that were converted into the corresponding pyrroles by Lewis acid-catalyzed ring closure. A screening of several Lewis/Brønsted acid catalysts was also performed.Keywords: alkynes; 1,2-diaza-1,3-butadienes; hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…3 J C,H of Z isomers 3.4-3.6 Hz). [17] We have observed that the N-cyclohexyl a-(N-enamino)-hydrazono compounds 5a-f are only in the E forms, while the N-benzyl a-(N-enamino)-hydrazones 5g-j are obtained as a mixture of E/Z isomers (E 55-80%, Z 14-28%). [17] The X-ray diffraction study of (E)-5h (Figure 1) unambiguously supports the assigned structure.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…3 J C,H of Z isomers 3.4-3.6 Hz). [17] We have observed that the N-cyclohexyl a-(N-enamino)-hydrazono compounds 5a-f are only in the E forms, while the N-benzyl a-(N-enamino)-hydrazones 5g-j are obtained as a mixture of E/Z isomers (E 55-80%, Z 14-28%). [17] The X-ray diffraction study of (E)-5h (Figure 1) unambiguously supports the assigned structure.…”
Section: Resultsmentioning
confidence: 96%
“…[17] We have observed that the N-cyclohexyl a-(N-enamino)-hydrazono compounds 5a-f are only in the E forms, while the N-benzyl a-(N-enamino)-hydrazones 5g-j are obtained as a mixture of E/Z isomers (E 55-80%, Z 14-28%). [17] The X-ray diffraction study of (E)-5h (Figure 1) unambiguously supports the assigned structure. [21] We have then explored the conversion of the aaminocarbonyl-a-(N-enamino)-hydrazones 5a-j into the corresponding pyrroles 8a-g by acid-catalyzed intramolecular ring closure.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Pursuing our long-standing interest in the chemistry of heterocycles, we have recently reported a novel synthetic route to highly functionalized pyrroles. [14] Specifically, the process was realized by a preliminary addition of a primary amine to a 1,2-diaza-1,3-diene (DD), [15] a hydroamination reaction with an activated alkyne producing an a-(N-enamino)-hydrazone and a subsequent Lewis acid-catalyzed ring closure by means of intramolecular C-nucleophilic attack to give the pyrrole heterocycle (El 1 + Nu!I 1 + El 2 !4'; Scheme 1, A).…”
Section: Introductionmentioning
confidence: 99%